The physico-chemical properties of 2-methoxyphenoxyacetates of Mn(II), Co(II), Ni(II) and Cu(II) - Ferenc, Wieslawa; Bernat, Maria; Sarzyński, Jan (Eclética Química, 2010)
The complexes of 2-methoxyhenoxyacetates of Mn(II), Co(II), Ni(II) and Cu(II)with the general formula: M(C9H9O4)3·4H2O, where M(II) = Mn, Co, Ni and Cu have been synthesized and characterized by elemental analysis, IR spectroscopy, magnetic and thermogravimetric studies and also X-ray diffraction measurements. The complexes have colours typical for M(II) ions (Mn(II) - a pale pink, Co(II) - pink, Ni(II) - green, and Cu(II) – blue). The carboxylate group binds as monodentate and bidentate ligands. On heating to 1273K in air the complexes decompose in the same way. At first, they dehydrate in one step to anhydrous salts, that next decompose to the oxides of respective metals with the intermediate formation of the oxycarbonates. Their solubility in water at 293K is of the order of 10-5 mol·dm-3. The magnetic moments of analysed complexes were determined in the range of 76-303K. The results reveal them to be high-spin complexes of weak ligand fields.